Hubungan Rinosinusitis Kronik Dengan Rinitis Alergi - Muslim Kasim; Neno Fitriyani H; Rakha Muhhamad Buchori (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Allergic rhinitis is an inflammatory disease caused by an allergic reaction in patients who have a history of atopy who have previously been sensitized with the same allergens. In Indonesia, the prevalence of allergic rhinitis varies between 1.5% - 12% and has increased every year. Many etiological and predisposing factors that can cause chronic rhinosinusitis include ARI due to viruses, various types of rhinitis, especially allergic rhinitis. This type of research is an observational analytic study with a cross-sectional study design. The data used are secondary data with medical record data in the ENT Polyclinic, Bintang Amin Hospital, Bandar Lampung in 2018-2019. Relationship analysis was performed using the Chi-Square test. Then the data that has been obtained is processed using the Statical Product and Service Solution (SPSS) program. Respondents with an HbA1c value≥9% were 31 people (63.3%), while Obtained respondents with the frequency distribution of allergic rhinitis in Bintang Amin Hospital Bandar Lampung in 2018-2019 with a frequency of 26 people (63.4%). Respondents with Chronic rhinosinusitis frequency distribution in Bintang Amin Hospital in Bandar Lampung in 2018-2019 were 25 people (61.0%). The Relationship between Chronic Rhinosinusitis and Alerfi Rhinitis in Bintang Amin Hospital in Bandar Lampung in 2018-2019. Evidently there is a relationship with p> 0.006 tested by Chi-Square. Which means there is a relationship between chronic rhinosinusitis and allergic rhinitis